Bruton's Tyrosine Kinase as a New Therapeutic Target - Uckun, Fatih M.; Tibbles, Heather E.; Vassilev, Alexei O. (Anti-Cancer Agents in Medicinal Chemistry, 2007)
Targeting Bruton's tyrosine kinase (BTK) with a small molecule inhibitor may be useful in treatment of BTK-expressing malignancies because of the anti-apoptotic function of BTK in cancer cells. Furthermore, BTK inhibitors also exhibit anti-thrombotic properties that may be desirable in the context of the increased risk of thromboembolic complications in cancer patients. This review will focus on the role of BTK in drug resistance in cancer, thromboembolism, and various pathologic immune responses, such as graft versus host disease. The therapeutic potential of targeting BTK is illustrated by discussion of the biologic activity profile of the rationally designed BTK inhibitor LFM-A13.
Keywords: cancer